Pengujian Usability untuk Aplikasi Silsilah Keluarga FamilySearch Tree dengan Pendekatan Kuantitatif - Audrey Chyara Luthsa Hannita Dharma; Ismiarta Aknuranda; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
The formation of a family in Islam is very upholding the problem of nasab or heredity, to support this it is necessary to have effective management of family tree information. One of the technologies that can support this is the FamilySearch Tree application, which is a genealogy software based on mobile application to create family structures digitally. An evaluation is needed to find out the advantages and disadvantages of application to the needs of Muslims, especially in terms of usability. The usability components tested were effectiveness, efficiency, and satisfaction. This study uses the usability testing method and the filling out of the Single Ease Question (SEQ) and System Usability Scale (SUS) questionnaire. This study is also useful to explore whether this application can meet the needs of Muslims about the text that is obtained from filling out the Close Ended questionnaire. This research is primarily quantitative. Participants in this study are generation Z with an age range of 13-25 years, totaling 30 who are new users of the FamilySearch Tree application and are Muslim. Usability testing is done to determine the effectiveness and efficiency components while filling out the questionnaire to determine the satisfaction component. Evaluation results show the effectiveness (completion rate) component yields 64.45%, which means it is low with the resulting error component being 42,03% which is still considered reasonable. In the efficiency component, the value is 0.030 goals / sec and 67.55%. And the satisfaction component of the SUS questionnaire is 39.1. For the closed ended questionnaire results obtained 57% which means this application has been able to meet the needs of Muslims about nasab. Keywords: usability testing, FamilySearch Tree application, SEQ, SUS, Close Ended Questionnaire